Lactococcus lactis and Lactobacillus sakei as bio-protective culture to eliminate Leuconostoc mesenteroides spoilage and improve the shelf life and sensorial characteristics of commercial cooked bacon. (September 2016) - Comi, Giuseppe; Andyanto, Debbie; Manzano, Marisa; Iacumin, Lucilla
Abstract: Cooked bacon is a typical Italian meat product. After production, cooked bacon is stored at 4 ± 2 °C. During storage, the microorganisms that survived pasteurisation can grow and produce spoilage. For the first time, we studied the cause of the deterioration in spoiled cooked bacon compared to unspoiled samples. Moreover, the use of bio-protective cultures to improve the quality of the product and eliminate the risk of spoilage was tested. The results show that Leuconostoc mesenteroides is responsible for spoilage and produces a greening colour of the meat, slime and various compounds that result from the fermentation of sugars and the degradation of nitrogen compounds. Finally, Lactococcus lactis spp. lactis and Lactobacillus sakei were able to reduce the risk of Leuconostoc mesenteroides spoilage. Highlights: The cause of greening and slime formation in cooked bacon was investigated. Leuconostoc mesenteroides resulted responsible for spoilage. Leuc. mesenteroides produced green colour, slime and various negative compounds. Lactococcus lactis spp. lactis and Lactobacillus sakei were able to inhibit the growth of Leuc. mesenteroides . Bio-protective culture were able to reduce the risk of spoilage.